Building type basics for justice facilities - Phillips, Todd S. (John Wiley, 2003)
Here's the in-depth information you need to initiate designs for a variety of justice facilities, including law enforcement, adult detention, courts, corrections, juvenile and family justice, and multi-occupancy facilities.